Matrimonial property division through philanthropic settlement / Noorul Huda Binti Sahari …[et al.] - Sahari, Noorul Huda; Mohd. Zain, Najibah; Ab. Manan, Siti Khadijah; Saedon, Rafeah; Muhd Hashim, Nurhidayah (Academy of Contemporary Islamic Studies, UiTM Shah Alam, 2015)
This study aims to examine the practice of sulh (mutual agreement) in dividing matrimonial asset after divorce, upon the death of a spouse and polygamous marriage. The study adopted qualitative method where analysis is conducted on a purposive sampling of unreported cases collected within the period of 2000- 2012. The samples are collected from six zones representing Shariah Courts in Malaysia. Analysis on the sampling is made based on several variables such as the types of matrimonial property, factors for consideration and proportion of distribution of the assets. This study discovers that philanthropic element of kindness, gift and generosity has been implemented in the majority of cases involving claims of a matrimonial property when they are practically settled by way of sulh (amicable settlement). In determining the division through sulh, the parties is in fact more generous when dealing with the interest of children to the level that the husband is willing to transfer the whole interest in the asset to the existing wife who is rarely achieved in other litigation processes. The parties also voluntarily waive each party right by granting the matrimonial asset as a gift to the children. This study suggests that the mutual consent on proportion of asset by way of sulh to be widely practised when dealing with the division of matrimonial assets to promote harmonious settlement and to prevent a costly and lengthy litigation process. This study suggests for specific governing mechanism in ensuring the establishment of justice among the disputing parties.